(untitled) (Applied Biological Research, 2020)
The natural habitats of Indian catfish (Heteropneustes fossilis) are generally known for less oxygen and most often polluted water bodies. The present study was aimed to understand the adaptability in terms of antioxidant defense mechanism at transcript levels. The studyconsidered key transcripts such as superoxide dismutase 2 (sod2), catalase (cat), glutathione peroxidase 4 (gpx4), and heat shock protein 70 (hsp70), heat shock cognate 70 (hsc70), hypoxia inducible factor 1alpha (hif1a) of the catfish exposed to a drying mud-bed while dwelling inside mud-peat under semidry conditions for 15, 30 and 45 days. The study revealed that desiccation stress triggered complicated oxidative stress. The cat, sod2 and gpx4 and hsp70 mRNA expressions significantly up-graded in the mud-dwelled fish. Further, mud dwelling also resulted in significant increase in the expression of hif1α in gills and muscle of fish after 30 days, suggesting its role as a vital regulator that carries out important alterations in gene expression under hypoxic stress. Collectively, the observations suggested that stress condition resulted in the development of oxidative stress, and H. fossilis was able to respond through alterations in stress responsive genes to survive semi-dry conditions.